THE INFLUENCE OF INSTITUTIONAL OWNERSHIP, MANAGERIAL OWNERSHIP, AND AUDIT COMMITTEE ON FINANCIAL STATEMENT INTEGRITY - Margaretha, Yezza Aprelya; Rochayatun, Sulis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The integrity of financial reporting is an important characteristic of good financial reporting, including honesty and avoidance of manipulation. Manipulation of financial reports can undermine integrity and pose serious risks to companies. Institutional ownership, managerial ownership, and audit committees are important in maintaining the integrity of financial statements. This study analyses and examines the impact of institutional ownership, management ownership, and audit committee on financial statement integrity. This study's population consisted of 62 mining companies listed on the Indonesia Stock Exchange (IDX) period 2020-2022. A purposive sampling technique was used for sampling. The samples obtained were 21 data from representatives of the seven mining sub-companies for three years. The analysis technique employed in this research is multiple linear regression. The findings indicate no significant impact of institutional ownership on the integrity of financial statements. Similarly, managerial ownership no significant impact on the integrity of financial statements. Additionally, the integrity of financial statements is not affected by the presence of an audit committee.